Inclusion in Physical Education in Primary Schools - Dena Widyawan; Ibnu Sina (JUARA : Jurnal Olahraga, 2021)
The purpose of this study was to determine inclusive education in general physical education from the perspective and experience of physical education teachers in primary schools. The method used in this research is qualitative phenomenology. Four Physical Education teachers were the sample (2 men, 2 women) aged between 30 and 55 years and were collected by means of: photos, school documents, field notes, and semi-structured interviews. Bandura's social cognitive theory is used as the basis of the research. Outcome of thematic analysis: engaging in learning, adapting strategies to meet student needs, and moving beyond educational goals. In conclusion, inclusive education in physical education in primary schools is built by dynamic interactions between teachers' knowledge of disabilities, motivation to learn about students, children's needs, and learning objectives.